The Meaning of Conservatism - Scruton, Roger. author. aut Link
XIII, 206 p.
Keywords: First published in 1980, this contribution to political thought is a statement of the traditional conservative position. Roger Scruton challenges those who would regard themselves as conservatives, and also their opponents.